Enhanced access to publicly funded data for science, technology and innovation. (OECD Publishing, 2020)
In increasingly knowledge-based societies and economies, data are a key resource. Enhanced access to publicly funded data enables research and innovation, and has far-reaching effects on resource efficiency, productivity and competitiveness, creating benefits for society at large. Yet these benefits must also be balanced against associated risks to privacy, intellectual property, national security and the public interest. This report presents current policy practice to promote access to publicly funded data for science, technology and innovation, as well as policy challenges for the future. It examines national policies and international initiatives, and identifies seven issues that require policy attention.